Circulating Adipokine Levels in Nonobese Women With Polycystic Ovary Syndrome and in Nonobese Control Women: A Systematic Review and Meta-Analysis - Lin, Kainan; Sun, Xiaoting; Wang, Xiao; Wang, Hanchu; Chen, Xia (Frontiers in Endocrinology, 2021)
Levels of circulating adipokines in nonobese polycystic ovary syndrome (PCOS) patients have been reported in many studies. However, the results are inconsistent. The aim of this meta-analysis is to assess whether the levels of circulating adipokines are changed in nonobese PCOS relative to nonobese healthy controls. To identify eligible studies, a literature research was performed in the PubMed, Embase, and Web of Science databases without restricting by region, journal, or language. A total of 81 studies met the eligibility criteria. The meta-analysis showed that the circulating level of adiponectin (standardized mean difference [SMD]: -0.95; 95% CI: -1.36 to -0.53) was significantly decreased in nonobese PCOS patients. In contrast, the circulating levels of chemerin (SMD: 1.13; 95% CI: 0.08 to 2.18), leptin (SMD: 0.47; 95% CI: 0.13 to 0.81), resistin (SMD: 0.45; 95% CI: 0.03 to 0.88), and visfatin (SMD: 1.38; 95% CI: 0.68 to 2.09) were significantly increased in nonobese PCOS patients. There were no significant changes in the circulating levels of apelin (SMD: 0.32; 95% CI: -1.34 to 1.99), irisin (SMD: 1.01; 95% CI: -0.68 to 2.70), omentin (SMD: -0.37; 95% CI: -1.05 to 0.31), or vaspin (SMD: 0.09; 95% CI: -0.14 to 0.32). Thus, scientific evidence suggests that the circulating adipokine levels are altered in nonobese PCOS patients compared to nonobese healthy controls. Therefore, independent of the degree of obesity, dysregulated circulating adipokine levels might play important roles in the occurrence and development of PCOS.